- Literacinese ou da escrita [literária] com imagens... em movimento - Lima, Eliana Kiara Viana (2015)
This essay has been conceived and written in order to conduct a study on the relation between literature and films in the educational environments. It deals especifically with the production of audiovisual texts adapted from literary texts, involving students of the third high school series of the Federal Institute of Education, Science and Technology - Campus Araguatins. The main appeal of this research is to analyze the relation between literature and film in relation to the teaching of literature in high schools by proposing a different way of articulating Literature and Cinema, Education and Cinema in schools. The dissertation also intends to present the film as a way of producing knowledge and not merely as a teaching resource in the classroom and also to unveil the educational possibilities arisen by the film. In so doing, it should think of the cinema not as a secondary art to literature, but as an independent art itself, although based on the former. The research approach is qualitative. Data collection has been performed through research-action and organized dialogue with the students, by bringing to bear a discussion on the litefilmaker student s perception concerning cinema and its limits and potentialities for the teaching of literature. This research has been theoretically based on the thoughts of authors such as Walter Benjamin, Robert Stam and Adriana Fresquet. This work is also legible as a plea in favor of possibilities to contribute for both film adaptation studies and in its use in the teaching of literature.